Human-Nature Interface in William Cowper’s "The Poplar Field" and E.B.White’s "Once More to the Lake" - Nath, Arjun; Timalsina, Dhurba Prasad (Journal of Innovation in Academia, 2023)
This paper attempts to analyze William Cowper’s poem "The Poplar Field" and E.B. White’s essay "Once More to the Lake" from an ecocritical perspective. Ecocriticism explores the relationships between elements, human culture, and the physical environment as presented in literary texts. In their respective works, both Cowper and White address issues related to nature, the acknowledgment of social ecology within the natural world, and the necessity for humans to coexist with it while respecting ecological balance. Both literary texts delve into the unpleasant and devastating environmental degradation and the interface between humans and nature, which forms the core of ecocriticism. In this context, human culture is intricately connected to the physical world, affecting and being affected by it. The texts also highlight the issue of biodiversity degradation and the loss of natural beauty. Furthermore, they touch upon environmental philosophy and ecocriticism, assuming that the human world and the physical environment are closely interlinked. This perspective teaches us to be more humane and to reject an anthropocentric approach.